Internationalising Engineering Degrees : The Challenge of Multiple Accreditations : Final Report. - Alam, Firoz; Kootsookos, Alexandra; Jollands, Margaret; Chowdhury, Harun (Dept of Education and Training Australia, 2017)
Transnational engineering degrees, where the host nation is a signatory of the International Engineering Alliance, need accreditation from both the "host" and "home" nations' professional bodies. Dual accreditation, however, remains a difficult task as the learning outcomes required by each accrediting body can vary substantially. This is the final report from a project that quantified these differences, as a first step toward achieving the dual accreditation.